2023
DOI: 10.3390/pathogens12020184
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: Diabetes Perspective—Pathophysiology and Management

Abstract: Recent evidence relating to the impact of COVID-19 on people with diabetes is limited but continues to emerge. COVID-19 pneumonia is a newly identified illness spreading rapidly throughout the world and causes many disabilities and fatal deaths. Over the ensuing 2 years, the indirect effects of the pandemic on healthcare delivery have become prominent, along with the lingering effects of the virus on those directly infected. Diabetes is a commonly identified risk factor that contributes not only to the severit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 244 publications
0
15
0
1
Order By: Relevance
“…Of them, IR seems to be a pivotal factor, adscribed to low-grade inflammation [8]. Nevertheless, the pathophysiological and molecular mechanisms connecting PCS and T2DM are far from completely understood [4] and there is a paucity of studies addressing this relation [8]. Additionally, a previous study by our working group showed that subjects with PCS, along with slight but significant elevations of inflammatory markers, had marked sex differences in the inflammatory response [9].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Of them, IR seems to be a pivotal factor, adscribed to low-grade inflammation [8]. Nevertheless, the pathophysiological and molecular mechanisms connecting PCS and T2DM are far from completely understood [4] and there is a paucity of studies addressing this relation [8]. Additionally, a previous study by our working group showed that subjects with PCS, along with slight but significant elevations of inflammatory markers, had marked sex differences in the inflammatory response [9].…”
Section: Introductionmentioning
confidence: 99%
“…An important role in this mechanism is attributed to Th17 and Treg cells, along with the secretion of inflammatory factors [3]. In addition to DM-associated low-grade inflammation affecting peripheral insulin sensitivity (IS), other mechanisms driven by hyperglycemia may be involved, such as elevated synthesis of advanced glycation end products (AGEs) [4] or direct stimulation of viral proliferation [1].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diabetes and diabetes-related complications in COVID-19 patients are primarily due to the acute illness caused during the SARS-CoV-2 infection followed by the release of glucocorticoids, catecholamines, and pro-inflammatory cytokines, which were shown to drive hyperglycemia positively [ 23 ].…”
Section: Introductionmentioning
confidence: 99%